URINARY TRACT INFECTIONS CAUSED BY CANDIDA SPECIES IN CATHETERIZED PATIENTS IN THE INTENSIVE CARE UNIT: A CROSS - SECTIONAL STUDY AT HUE UNIVERSITY OF MEDICINE AND PHARMACY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Background: Urinary tract infections caused by Candida species are commonly encountered in patients treated in the Intensive Care Unit (ICU), particularly those with indwelling urinary catheters. Although Candida albicans has traditionally been reported as the predominant species isolated from the urinary tract, an increasing prevalence of non-albicans Candida species has been observed.Objectives: This study aimed (1) to determine the prevalence of urinary Candida infection among catheterized patients treated in the ICU at Hue University of Medicine and Pharmacy Hospital, and (2) to identify Candida species isolated from urine specimens.Materials and Methods: A descriptive cross-sectional study was conducted among 47 catheterized patients receiving treatment in the ICU of the Department of Anesthesiology - Intensive Care –Emergency - Toxicology at Hue University of Medicine and Pharmacy Hospital from May 2024 to May 2025. Urine samples were collected and cultured for fungal isolation and species identification.Results: The prevalence of urinary Candida infection was 63.8%, and the prevalence of a fungal colony count ≥ 10³ CFU/mL was 57.4%. Five Candida species were isolated. Candida tropicalis was the most prevalent species (45.5%), followed by Candida albicans (33.3%), whereas other non-albicans Candida species accounted for 21.2%. Single-species isolation was observed in 86.7% of urine samples, while mixed infections involving two fungal species were identified in 13.3% of samples.Conclusions: Non-albicans Candida species were more frequently isolated than Candida albicans in urine specimens from catheterized ICU patients (66.7% vs. 33.3%), with Candida tropicalis being the predominant species.
Keywords: Candida, fungal urinary tract infections, ICU.